Produksi Jagung Pada Berbagai Jarak Tanam Dalam Sistem Tumpangsari Jagung - Kacang Tanah, Jagung - Kacang Kedelai, Jagung - Kacang Hijau - La Musadi; Margo Yuwono (Fakultas Pertanian Universitas Papua, 2009)
The aim of this experiment was to find the ideal plant spacing to give the best growth of multicropping system between corn - peanut, corn - soybean and corn – green bean. This experiment was conducted at SP II Prafi district from June to October 2006 using completely randomized design which consists of six forms of plant spacing in three replicates. The treatments are100 cm x 25 cm (A1D1), 100 cm x 50 cm (A1D2), 150 cm x 25 cm (A2D1), 150 cm x 50 cm (A2D2), 200 cm x 25 cm (A3D1) and 200 cm x 50 cm (A3D2). The results showed that narrow plant spacing gave the best yield per plot while the lowest yield performed by wide plant spacing